The interplay between national interest and Idealism regarding Sweden’s Gripen exports - Coetzee, Wayne (Scientia Militaria - South African Journal of Military Studies, 2017)
The study on which this article is based, aimed to map out and analyse the ways in which Sweden’s Gripen exports have been shaped and sustained since the end of the Cold War. It did so by examining three interrelated factors that have had an effect on Sweden’s defence industry. By illustrating how societal preferences, defence and security policy shifts, and the role of national identity have influenced weapons manufacturing and exports, this article provides a balanced overview of the most salient push and pull factors of Sweden’s Gripen exports. The central contention of the study was that Swedish weapons manufacturing and exports often involve a close interaction between interests and ideals. Moreover, due to the multitude of richly correlated, interconnected and mutually reinforcing elements related to such practices, there cannot be a neat and parsimonious distinction between agents and structures and domestic and international settings. Instead, the study was especially reflective of real-world practices and the strategic relational approach between those forces that shape and sustain Sweden’s Gripen exports.